Development of a method for finding the optimal solution when upgrading a motorcycle engine - Vrublevskyi, Oleksandr; Wojnowski, Radomir (Technical Sciences, 2019)
This paper describes a method for finding the optimal parameters of a spark-ignition engine gas exchange system for a motorcycle. The vectors of the initial data for filling the parameter space, in which the search for the optimal solution has been made, have been formed through methods of experiment planning and technique nonlinear programming quadratic line search. As the quality criteria, the engine power has been used at selected points of the external speed characteristic. The results of the work have shown how using the proposed optimization method allows modernization of a gas exchange systems in order to increase the engine power.